2014
DOI: 10.5152/dir.2014.14008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of PET/MRI: current status and future perspectives

Abstract: Fully integrated positron emission tomography (PET)/magnetic resonance imaging (MRI) scanners have been available for a few years. Since then, the number of scanner installations and published studies have been growing. While feasibility of integrated PET/MRI has been demonstrated for many clinical and preclinical imaging applications, now those applications where PET/MRI provides a clear benefit in comparison to the established reference standards need to be identified. The current data show that those partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(56 citation statements)
references
References 68 publications
0
52
0
4
Order By: Relevance
“…High cost and high levels of radiation exposure are the main limitations of PET-CT. In contrast, PET-MRI, a novel hybrid imaging technique, causes a lesser amount of radiation exposure (49). Despite the absence of any conclusive data, it may presumably replace PET-CT in the follow-up of AE cases.…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…High cost and high levels of radiation exposure are the main limitations of PET-CT. In contrast, PET-MRI, a novel hybrid imaging technique, causes a lesser amount of radiation exposure (49). Despite the absence of any conclusive data, it may presumably replace PET-CT in the follow-up of AE cases.…”
Section: Treatment and The Role Of Interventional Radiologymentioning
confidence: 99%
“…MRI, on the other hand, offers a sensitivity superior to that of CT concerning infiltration of the primary tumor into adjacent organs and detection of metastasis to parenchymatous organs such as the liver, brain, or kidneys (6)(7)(8). In addition, MRI provides valuable functional information from quantitative and multiparametric imaging (9). With the introduction of fully integrated PET/MRI systems, PET and MRI can be used synergistically in a single modality, taking advantage of an exact correlation between 18 F-FDG-avid lesions and the anatomic details obtained by MR images (10)(11)(12)).…”
mentioning
confidence: 99%
“…Previous studies have revealed that PET/MR provides good performance in the investigation of brain function, tumor, and degenerative diseases (1). The combined MRI system not only delivers detailed brain anatomy, but also can make PET image quality better by correcting partial-volume effects or motion artifacts (2,3).…”
mentioning
confidence: 99%